Figures, Structures, and Symbols: Nur Muttaqin's Winning Strategy in the 2024 General Election in Ciamis Regency - Ela Nurlaela; Iim Rahmatilah; Resti Nurwinawati; Muhammad Dzulfan G; Regi Refian Garis (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
This research aims to examine the winning strategy implemented by Nur Muttaqin as a legislative candidate from the Democratic Party in the 2024 election in Ciamis Regency. Using a qualitative approach and data collection techniques in the form of in-depth interviews, documentation, and digital observation, this study found that the winning strategy is built through two main approaches: internal strategies in the form of party structure consolidation and political education; and external strategies through community aspiration services and locality-based symbolic communication. The findings are reinforced by political mobilization theory (Verba et al., 2020) and contextual political communication (Canel & Voltmer, 2020). The results show that figurative and relational approaches are the main keys to gaining the most votes within the party, with Nur Muttaqin receiving 7,054 valid votes. This research contributes significantly to the understanding of campaign strategies in the context of local politics and open proportional systems. Keywords: Political Strategy, 2024 Elections, Party Mobilization, Political Communication, Nur Muttaqin, Ciamis.